The certified manager of quality/organizational excellence handbook - Westcott, Russ, 1927- (ASQ Quality Press, 2013)
This handbook is a comprehensive reference source designed to help professionals address organizational issues from the application of the basic principles of management to the development of strategies needed to deal with the technological and societal concerns of the new millennium. The content of this fourth edition has been revised to reflect a more current global perspective and to match the updated Body of Knowledge (BoK) of ASQ's Certified Manager of Quality/Organizational Excellence (CMQ/OE). In order to provide a broad perspective of quality management, this book has specifically been.
Keywords: Total quality management -- Handbooks, manuals, etc.; elektronické knihy; electronic books